Le Corbusier - Rappaport, Alexander (project baikal, 2019)
Charles Edouard Jeanneret who changed his name to the symbolic Le Corbusier was the author of a hundred of buildings, dozens of books and articles, a symbol of the age and the culture and an iconic man. The logic of Le Corbusier and the rhetoric of his demonstrations, his theory and practice are supported by his skills in individuation and persuasion with a thing. The role of Corbu’s cousin Pierre in their creative work has not been revealed yet. Le Corbusier was a great man, but Man was not his real hero.
Keywords: Le Corbusier; Pierre Jeanneret; the language of contemporary architecture; paradoxes